First Year Gastrointestinal Endoscopy Profile in Singkawang West Borneo 2017 – 2018 - Frandy Frandy; Prionggo Mondrowinduro (The Indonesian Society for Digestive Endoscopy, 2018)
Background: Gastrointestinal endoscopic examination which is included in the referral system of the Badan Penyelenggara Jaminan Sosial (BPJS) has been available at St Vincentius Hospital Singkawang and already been conducted by internist since March 2017 to diagnose upper and lower gastrointestinal diseases. The gastrointestinal endoscopic examination unit serves referrals from Singkawang and its 3 surrounding districts (Sambas, Bengkayang, and Mempawah) that close to the Malaysian border. The purpose of this study is to determine the patients’ profile from Singkawang, Sambas, Bengkayang, and Mempawah Districs who underwent gastrointestinal endoscopic examination at St Vincentius Hospital from March 2017 to April 2018.Method: This is a retrospective descriptive study by using secondary data of patient’s medical records at St Vincentius Hospital Singkawang in March 2017 - April 2018. Every patient is included as a sample (total sampling). Total numbers are consisted of 308 patients including 230 esophagogastroduodenoscopies and 78 colonoscopies.Result: The results of this study showed that majority of patients were more likely to undergo esophagogastroduodenoscopy (EGD) (75%) than colonoscopy (25%). Males, age group of 51-70 years old and Malay ethnic are the groups of patients who have the most upper and lower gastrointestinal disorders. The prominent finding of esophagogastroduodenoscopy was erosive gastritis (64%), whereas internal hemorrhoids was the most common finding in colonoscopy (67%); if internal hemorrhoids was excluded, colon mass became the most common finding disorder.Conclusion: Patient were mostly male, age group between 51 – 70 years old and Malay. The most common finding in colonoscopy (67%); if internal hemorrhoids was excluded, colon mass shifted forward as the top finding disorder.